Hubungan Ketinggian Tempat Dan Kemiringan Lereng Tehadap Produksi Kopi Arabika Sigarar Utang Di Kecamatan Lintong Nihuta - Leonard Sihite; Posma Marbun; Supriadi Supriadi (Universitas Sumatera Utara, 2015)
The purpose of the study was to know the location with the highest production of arabicca coffee(Coffea Arabica) in Lintong Nihuta regency of Humbang Hasundutan. The study was done withcorelating map of place height, map of slope, map of ground tipe. After overlaying map of groundtipe, elvation, and slope it was found 31 SPT (set of land) with the scale 1 : 25.000. The populationof the research is coffee tree in the study field. Sum of point of sampling for coffee trees are 390sample points. The result of data analysis showed the higest sum of ripe seed coffe production atSiponjot village as SPL (set of land) 12 and the lowest sum of ripe seed coffee production atPargaulan village as SPL 3. The highest weight production of ripe seed coffee production atSiponjot village as SPl (set of land) 12 and the lowest weight production of ripe seed coffeeproduction at Lobutua Village as SPL 2. The highest weight production of dry seed coffee atSibuntuon Parpea as SPL 8 and the lowest weight production of dry seed coffee at PargaulanVillage as SPL 3.Keywords : Height Place, Slope, Coffee Production